Practical Skill Improvement Needs of Technical College Mechanical Engineering Craft Practice Curriculum in Nigeria - B.N., Atsumbe; ., Ogwo B.A (Journal of Education and Vocational Research, 2012)
In recent years, the curriculum of technical college mechanical engineering craft practice has been criticized as being shallow and inadequate. Because of this deficiency, the study was therefore designed to determine the needed practical skills improvement on the curriculum of technical college mechanical engineering. One research question and a hypothesis guided the study. The study was conducted in the North Central States of Nigeria. A survey research design was employed. Twenty-eight (28) industries were sampled for the study. Using purposive sampling sixty (60) mechanical engineers, one hundred technicians (100) and one hundred and fifty craftsmen were used for the study. A forty-eight item questionnaire was used for the study. A forty-eight item questionnaire was used to collect data, and data analysis was done using Mean, Standard Deviation, and One Way Analysis of Variance (ANOVA). Findings showed that respondents agreed with the items with a very high mean of 3.50 – 3.83, areas that attracted high mean included advanced machining, material treatments and engineering drawing. It was recommended that these new items should be incorporated into the curriculum during review.